2016
DOI: 10.1017/s1368980016000550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal exposure to polycyclic aromatic hydrocarbons from maternal diet on birth outcomes: a birth cohort study in Korea

Abstract: Objective: Polycyclic aromatic hydrocarbons (PAH) are common dietary exposures that cross the human placenta and are classified as a probable human carcinogen. The aim of the present study was to investigate the potential impact of exposure to PAH-containing meat consumed during pregnancy on birth outcomes. Design: Prospective birth cohort study. Only non-smoking women with singleton pregnancies, who were free from chronic disease such as diabetes and hypertension, were included in the study. Maternal consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 59 publications
1
8
2
Order By: Relevance
“…The discrepancy between studies may be due to different naphthalene exposure levels. The median concentration of urinary 2-OH NAP (6.34 μg/g) in the present study was higher than that observed in the study by Lamichhane et al (9.96 ng/g) [18] and Herbstman et al (3.11 μg/g) [36]. Jing JQ et al [22] showed that the highest emission load among 16 PAHs was naphthalene in Taiyuan, with a 39.18% contribution rate.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The discrepancy between studies may be due to different naphthalene exposure levels. The median concentration of urinary 2-OH NAP (6.34 μg/g) in the present study was higher than that observed in the study by Lamichhane et al (9.96 ng/g) [18] and Herbstman et al (3.11 μg/g) [36]. Jing JQ et al [22] showed that the highest emission load among 16 PAHs was naphthalene in Taiyuan, with a 39.18% contribution rate.…”
Section: Discussioncontrasting
confidence: 77%
“…Polanska et al [16] detected a link between the sum of hydroxyphenanthrene levels and the higher cephalization index (CI). The relationship between 1-hydroxypyrene (1-OH PYR) and birth outcomes has also been investigated in previous studies [9, 17, 18]. However, the association between naphthalene exposure and birth outcomes has rarely been tested in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that maternal dietary (215) (180) and airborne PAH (215) exposure as well as PAH-DNA adduct levels in newborns (314) (315) are associated with reduced birth weight. Conversely, prenatal and early exposure to PAHs is positively associated with increased BMI, obesity, and waist circumference in childhood (197) (335) (346).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…It can affect the intelligence of children as well as causing respiratory problems, since they are more sensitive to such contaminants than adults (Edwards et al, 2010;Lamichhane et al, 2016;Song et al, 2013). There are many studies on the exposure of pregnant women, such as heavy metal exposure (Kim et al, 2011;Pola nska et al, 2014), pesticide exposure (Yu et al, 2016;Wang, Chen, et al, 2017), mycotoxin exposure (Lei et al, 2013;Sarkanj et al, 2013), passive smoking exposure (Baheiraei et al, 2012), and so on.…”
Section: Introductionmentioning
confidence: 99%